PENGARUH PENYULUHAN TERHADAP KEPUTUSAN PETANI DALAM ADOPSI TEKNOLOGI PENGENDALIAN HAMA TERPADU PADI SAWAH DI KECAMATAN CIKALONGKULON - Farisa Nabila Fitri Rahmasari; Dedy Kusnadi; Harniati Harniati (Jurnal Inovasi Penelitian, 2020)
UU no. 12 of 1992 concerning crop cultivation and PP No. 6/1995 mandates that pest control be carried out by Integrated Pest Management (IPM). In Cianjur, extension activities are used as a method that is often used by agricultural officers in conveying the latest information and technology to farmers in order that the technology can be adopted by farmers. This research was conducted in Majalaya Village, Cikalongkulon District, Cianjur Regency in April - June 2020. The sample in this study amounted to 40 people who were determined by the judgment and quota sampling methods. Analysis of the data used in this research is descriptive analysis, and multiple linear regression analysis. The results showed that the level of adoption of new farmers to the level of knowledge is in the medium category, the persuasion is still not good, the majority of farmers still do not agree and have not applied IPM technology. The factors that influence it simultaneously are: farmer characteristics, extension activities and characteristics of technological innovation. While partially that is the length of formal education and the characteristics of technological innovation. The strategy that can be carried out to accelerate farmers' decisions in adopting IPM technology is by introducing deeper knowledge of blast disease integrated pest control technologies along with the innovative characteristics of the technology with an approach through extension.